Climate change may induce connectivity loss and mountaintop extinction in Central American forests - Lukas Baumbach (Nature Portfolio, 2021)
Baumbach et al. investigate impacts of climate change on tree species within tropical forest ecosystems in Central America. Their models suggest large transitions from wet to generalist or dry species, reduced connectivity for wet forest species, and upslope shifts of montane species, causing risk of extirpation.